2014
DOI: 10.1039/c4em00262h
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium discharge from paddy fields with different initial scrapings for decontamination after the Fukushima Dai-ichi Nuclear Power Plant accident

Abstract: To explore the behavior of radionuclides released after the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) accident in March 2011, and the distribution of radiocesium in paddy fields, we monitored radiocesium (Cs) and suspended sediment (SS) discharge from paddy fields. We proposed a rating scale for measuring the effectiveness of surface soil removal. Our experimental plots in paddy fields were located ∼40 km from the FDNPP. Two plots were established: one in a paddy field where surface soil was not removed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Alternatively, remediation efforts could be concentrated before July or after October, when typhoons are unlikely to occur. We do not recommend mixing soil with water (puddling) in contaminated fields, as this could export the contamination contained in the uppermost layers of the soil (Wakahara et al, 2013). Furthermore, contaminated soils that have been eroded and transported by the river could be deposited on top of already decontaminated soil (Sakai et al, 2014).…”
Section: Implications For Contamination Redistribution Across the Catmentioning
confidence: 96%
“…Alternatively, remediation efforts could be concentrated before July or after October, when typhoons are unlikely to occur. We do not recommend mixing soil with water (puddling) in contaminated fields, as this could export the contamination contained in the uppermost layers of the soil (Wakahara et al, 2013). Furthermore, contaminated soils that have been eroded and transported by the river could be deposited on top of already decontaminated soil (Sakai et al, 2014).…”
Section: Implications For Contamination Redistribution Across the Catmentioning
confidence: 96%
“…When paddies are puddled for the rice growing season, they are flooded with water potentially containing suspended sediment and adsorbed radiocesium (Endo et al, 2013;Wakahara et al, 2014;Yoshikawa et al, 2014). Further, when the paddies are drained, they are directly connected to the stream network and may become a significant source of sediment and radiocesium, as water and sediments discharged from paddy fields are often transferred directly to stream systems .…”
Section: Radiocesium Hillslope Transfersmentioning
confidence: 98%
“…Quantifying hillslope erosion is difficult for Japanese paddy fields as they may be both sources and sinks of sediment and sediment-bound radiocesium (Tanaka et al, 2013b;Wakahara et al, 2014). When paddies are puddled for the rice growing season, they are flooded with water potentially containing suspended sediment and adsorbed radiocesium (Endo et al, 2013;Wakahara et al, 2014;Yoshikawa et al, 2014).…”
Section: Radiocesium Hillslope Transfersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous dosimetric studies demonstrated that currently the internal exposure of both the local population and the decontamination workers remains minimal, both internal and external exposures of these groups should be studied over longer temporal periods to help understand the longterm impacts of this accident on exposed population groups. More research is also required to understand the fate and dynamics of other longer-lived radionuclides in the Fukushima www.soil-journal.net/5/333/2019/ SOIL, 5, 333-350, 2019 region including radiocarbon (Paterne et al, 2018;Povinec et al, 2016;Xu et al, 2016), plutonium and uranium isotopes (Jaegler et al, 2018;Zheng et al, 2013;Steinhauser, 2014) as they may be persistent in the environment even though many were emitted only at the trace and ultra-trace levels.…”
Section: Perspectives For Future Researchmentioning
confidence: 99%